New religious movement responses to COVID - Benjamin Zeller (Donner Institute, 2021)
New religious movements (NRMs) have responded to the COVID-19 pandemic in diverse ways, ranging from closely following mainstream public health recommendations to explicit rejection of such guidance. This article considers the manner in which NRMs have responded to the pandemic through analysis of groups’ ideological alignment with their host societies’ cultural and social frames. Extending the Bromley–Melton (2012) model of social alignment and the Rochford (2018) approach of frame alignment, the response of these NRMs must be contextualized in regard to alignment with broader social frames. The article considers specific cases of NRMs in South Korea, India, and the United States and posits that no single model can encompass NRM responses to the pandemic, but that multiple social factors provide guidance for understanding why and how NRMs responded to the COVID-19 pandemic.